The cleanliness differences of root canal irrigated with 0.002% saponin of mangosteen peel extract and 2.5% NaOCl - Anis Sakinah; Laksmiari Setyowati; Devi Eka J (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Root canal treatment consists of preparation, sterilization, and obturation. During root canal preparation, debris is smeared over the dentinal surface forming a smear layer. Smear layer will reduce the attachment of root canal filling materials. Organic material in smear layer can be substrated for microorganism. Preparation of root canal should be followed by irrigation. NaOCl is common irrigation solution in endodontics. It has been very effective for their disinfecting and tissue-dissolving properties, but it is incapable of removing the smear layer. On the other hand, saponin of mangosteen peel extract has an ability as a surfactant to lower the surface tension, and it can dissolve debris containing of anorganic and organic materials. Purpose: This study aims to know the differences between 2.5% NaOCl and 0.002% saponin of mangosteen peel extract in removing the debris in the root canal after the preparation procedure. Method: Three groups of teeth (7 teeth in each) were instrumented with K-file and irrigated as follow: group 1 (control) with aquadest; group 2 with 2.5% NaOCl; and group 3 with 0.002% saponin of mangosteen peel extract. Furthermore, those teeth were split horizontally and longitudinally 4mm above the apical. The apical third of root canal walls was observed by a scanning electron microscope (SEM). Result: There were significant differences between each group (p<0.05). Median value of the group 3 was score 1 considered as the smallest value. It indicates that Group 3 with 0.002% saponin of mangosteen peel extract was the cleanest group. Conclusion:It can be concluded that 0.002% saponin of mangosteen peel extract can clean the smear layer of the root canal better than 2.5% NaOCl.